Uma proposta de jogo digital para ajudar no combate a fome no Brasil - Miranda, Frederico Severo; Stadzisz, Paulo Cezar (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES); 2018: Anais do III Workshop sobre Aspectos Sociais, Humanos e Econômicos de SoftwareDO - 10.5753/washes.2018.3478, 2018)
Hunger is currently a global problem, reaching 805 million people around the world and 3.4 million brazilians. This is a complex problem that will be eradicated with a better distribution of food and actions of governments and society. The FreeRice web game aims to combat hunger by converting virtual foods into real ones. This article proposes to implement the idea of FreeRice in a 3D virtual platform to help reduce hunger in Brazil.